Nuclear energy: addressing the not-in-my-backyard syndrome - Chew, Alvin (2016)
The nuclear power states have not resolved the issue of permanent storage of nuclear spent fuel. Countries with existing nuclear facilities also face challenges to the temporary storage of their spent fuels. What can other countries adopting nuclear energy learn from the experiences?